Effect of Aqueous Extract of Ageratum Houstonianum on Seed Germination and Seedling Growth of Triticum Aestivum (Wheat) - Budhathoki, Sumitra; Shakya, Bimala; Maharjan, Sanu Raja; Thapa, Lal Bahadur (Khwopa Journal, 2024)
Invasive plants are species that do not belong in a particular habitat but enter and establish themselves there. They are known for their adaptability and competitiveness in different environmental conditions. They tend to compete with crops for crucial resources, including water, light, and nutrients and can hinder crop growth and development through allelopathy. The aim of the current research was to investigate the allelopathic effect of aqueous extracts of Ageratum houstonianum on the germination and growth of wheat (Triticum aestivum) seedlings. The aqueous extracts were obtained from the leaves of A. houstonianum at various concentrations, including control, 25%, 50%, and 100%, and applied to pot and petri-plates cultures. The experiment was set up with 5 replicates for both the Petri plates and pot cultures. The study results showed that A. houstonianum aqueous leaf extracts had a significant impact on the germination and growth of T.aestivum. The concentrated (100%) aqueous leaf extracts of A. houstonianum significantly hindered the germination of seeds and growth parameters of T. aestivum. Additionally, the extract treatments of the weed species resulted in changes in soil pH and soil fertility. When invasive weed species grow alongside crops in fields, they may consume a significant number of resources required for crop growth, leading to a decrease in both the quantity and quality of agricultural output. Hence, this study highlights the potential adverse effects of invasive weeds on crop growth and development, and how they can negatively impact agricultural productivity. Therefore, there is a need for effective management strategies to control the spread of invasive weed species and preserve the productivity of agricultural land.